2013
DOI: 10.1289/ehp.1205682
|View full text |Cite
|
Sign up to set email alerts
|

Residential Proximity to Methyl Bromide Use and Birth Outcomes in an Agricultural Population in California

Abstract: Background: Methyl bromide, a fungicide often used in strawberry cultivation, is of concern for residents who live near agricultural applications because of its toxicity and potential for drift. Little is known about the effects of methyl bromide exposure during pregnancy.Objective: We investigated the relationship between residential proximity to methyl bromide use and birth outcomes.Methods: Participants were from the CHAMACOS (Center for the Health Assessment of Mothers and Children of Salinas) study (n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 27 publications
(36 reference statements)
3
31
1
2
Order By: Relevance
“…Agricultural workers were classified as exposed to this chemical group, among several other EDC groups, whereas pesticides was the only EDC group to which veterinarians and life science technicians were classified as exposed. In the past, exposure to pesticides among pregnant women has been widely investigated (Chevrier et al 2011; Gemmill et al 2013; Rauch et al 2012; Wickerham et al 2012), and our findings fall in line with other studies that have reported associations between reduced birth weight and maternal exposure to pesticides, both ambient and occupational (Burdorf et al 2011; Chevrier et al 2011; Wickerham et al 2012; Wohlfahrt-Veje et al 2011). However, these studies evaluated continuous birth weight, not term LBW.…”
Section: Discussionsupporting
confidence: 92%
“…Agricultural workers were classified as exposed to this chemical group, among several other EDC groups, whereas pesticides was the only EDC group to which veterinarians and life science technicians were classified as exposed. In the past, exposure to pesticides among pregnant women has been widely investigated (Chevrier et al 2011; Gemmill et al 2013; Rauch et al 2012; Wickerham et al 2012), and our findings fall in line with other studies that have reported associations between reduced birth weight and maternal exposure to pesticides, both ambient and occupational (Burdorf et al 2011; Chevrier et al 2011; Wickerham et al 2012; Wohlfahrt-Veje et al 2011). However, these studies evaluated continuous birth weight, not term LBW.…”
Section: Discussionsupporting
confidence: 92%
“…Using data from the California Pesticide Use Reporting (PUR) system, we estimated the total kilograms of OP and carbamate pesticides used in agriculture near the residence where each woman lived the longest during her pregnancy, applying methods that have been described in detail elsewhere (Gemmill et al 2013; Gunier et al 2011; Nuckols et al 2007). The California PUR system reports the pounds of active pesticide applied, the date of application, and the location, which is reported by one-square mile sections (approximately 1.6 km × 1.6 km) as defined by the Public Land Survey System (PLSS) (U.S.…”
Section: Methodsmentioning
confidence: 99%
“…We previously found that living within 5 km of methyl bromide use in the second trimester of pregnancy was associated with decreased birth weight, length, and head circumference (Gemmill et al, 2013). Methyl bromide was banned by the Montreal Protocol due to harmful effects on the ozone layer and is currently being phased out of use, resulting in increased usage of chloropicrin, metam sodium and 1,3-DCP in recent years (CDPR, 2016).…”
Section: Introductionmentioning
confidence: 99%